Triatoma dimidiata in Colombia: Distribution, ecology and epidemiological importance. (2023)
Triatoma dimidiata is an important vector of Chagas disease in Central America and countries of northern South America. In Colombia, it has a wide geographical distribution with reported presence in 14 departments in the Andean, Caribbean, Eastern plains and Upper Magdalena regions, where it occupies different natural and artificial ecotopes. The species is considered a secondary vector in the transmission of Trypanosoma cruzi. Its presence in wild, peridomestic and intradomiciliary habitats in the Andean region, coupled with its ability to move between them, has allowed it to escape the control based on pyrethroids spraying, highlighting its importance in maintaining transmission of the parasite through the potential reinfestation of homes.Understanding the relation of T. dimidiata and its habitats, as well as the empowerment of communities, will contribute to the development of effective and lasting control systems.The purpose of this review was to describe the distribution, risk factors, ecology, entomological features and habitats of T. dimidiata populations in Colombia, and to propose alternative interventions in agreement with the specific characteristics of the species.